XENO : the promise of transplanting animal organs into humans - Cooper, D. K. C. (David K. C.), 1939- (Oxford University Press, 2000)
The plight of a patient waiting months, sometimes years, for an organ transplant is one of the most heart-wrenching predicaments confronting medicine today. But the current critical shortage of human donor organs has had one positive consequence: it has stimulated promising new research into the field of xenotransplantation--the transplantation of organs from one animal species to another. In Xeno: The Promise of Transplanting Animal Organs Into Humans, David Cooper and Robert Lanza explore what may become one of the greatest medical advances of the 21st century. As scientists genetically engi.